Great Britain in the process of establishing Common Foreign and Security Policy of the European Union - Hrubinko, Andrii (Actual problems of law (Aktual'ni problemi pravoznavstva), 2020)
The article presents the results of the research position and role of the United Kingdom in the process of formation of the Common Foreign and Security Policy (CFSP) of the European Union at different periods of its development. There were considered the historical peculiarities of the East European policy of Great Britain, formation of its position on Ukraine’s European integration in the context of implementation of the CFSP and enlargement of the EU. The main conclusion is that Britain has neglected the EU leadership capabilities in the CFSP, which was objectively the optimal option to maximize the identification of its leadership ambitions in the Union. In the case of total withdrawal from the EU, the UK will be forced to abandon the CSDP. For the EU, Brexit can have both positive and negative consequences. Brexit will lead to a partial loss of its influence on regional processes and will have some negative consequences for the international positions of Ukraine.